FORMULATION, OPTIMIZATION, AND EVALUATION OF IN-SITU GEL OF MOXIFLOXACIN HYDROCHLORIDE FOR OPHTHALMIC DRUG DELIVERY - Gupta, Chitra; JUYAL, VIJAY; Nagaich, Upendra (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study emphasizes the synthesis, optimization, and evaluation of ocular in-situ gel for ophthalmic drug delivery against conjunctivitis. Methods: Pre-formulation studies on the drug and polymers were carried out, which included the study of various physicochemical properties of the drug and drug-polymer compatibility studies. The 12 different formulations were further pre-optimised by Taguchi method for determining the number of influential factors. Furthermore, the formulation optimization was done by using ‘Box–Behnken’ design (BBD) (Design expert 10 software) for assessing the effect of formulation variables on product characteristics viz. viscosity, gelation temperature (GT), and mean release time (MRT). About 13 suggested runs of the experiment were carried out and formulations were optimised. Finally, three batches of the optimised formulation were prepared and evaluated for in vitro drug release, isotonicity of formulation, anti-microbial potential, ocular irritancy, and accelerated stability testing. Results: Pre-formulation study confirmed the purity, solubility, and compatibility of drug measured by λmax, partition coefficient, stability study, and Fourier-transform infrared spectroscopy (FTIR) analysis. Taguchi screening method suggested about 12 different formulations and 3 most prominent influential factors including viscosity, GT, and drug release. 13 different formulations designed based on ‘BBD’ method were further optimised by considering the most influential factors suggested by Taguchi screening. The in vitro evaluation of the optimised formulation gave satisfactory results in terms of drug release, and anti-microbial activity. It was found to be isotonic with no ocular irritancy. Further, the preparation immediately transformed from sol to gel upon administration into cul-de-sac region of the eye due to multi-dimensional approaches utilised for in-situ gel formation namely temperature change Pluronic, ion sensitivity due to Gellan-gum, pH sensitivity because of Carbopol. Conclusion: The optimised in-situ gelling ocular drug formulation showed promising potency for ophthalmic drug delivery with no irritancy due to the multifactorial mechanism.